BERNARD RAHO AND RELIGION IN SOCIOLOGICAL PERSPECTIVE - Triansyah Fisa (Teunuleh Publisher, 2020)
Societal phenomena, religious activities that appear in the community are always the focus of attention for sociologists. Even religion is often referred to as one of the important institutional structures that complement the entire social system. This has clearly placed religion as a social institution that has different characteristics than other social institutions. This article will review how sociologists examine the religious phenomena that exist in society by focusing attention on the problem of the definition and characteristics of religion sociologically as well as discussions around the dual function of religion for society, especially as a force capable of uniting and at the same time divorcing a society, which always puts religion as a factor that is quite influential to the dynamics of society as a whole.